Anti-fibrotic therapy and lung transplant outcomes in patients with idiopathic pulmonary fibrosis - Todd L. Astor; Hilary J. Goldberg; Laurie D. Snyder; Andrew Courtwright; Ramsey Hachem; Tahuanty Pena; Lorenzo Zaffiri; Gerard J. Criner; Marie M. Budev; Tany Thaniyavarn; Thomas B. Leonard; Shaun Bender; et al. (Therapeutic Advances in Respiratory Disease, 2023)
Background: It is unclear whether continuing anti-fibrotic therapy until the time of lung transplant increases the risk of complications in patients with idiopathic pulmonary fibrosis. Objectives: To investigate whether the time between discontinuation of anti-fibrotic therapy and lung transplant in patients with idiopathic pulmonary fibrosis affects the risk of complications. Methods: We assessed intra-operative and post-transplant complications among patients with idiopathic pulmonary fibrosis who underwent lung transplant and had been treated with nintedanib or pirfenidone continuously for ⩾ 90 days at listing. Patients were grouped according to whether they had a shorter (⩽ 5 medication half-lives) or longer (> 5 medication half-lives) time between discontinuation of anti-fibrotic medication and transplant. Five half-lives corresponded to 2 days for nintedanib and 1 day for pirfenidone. Results: Among patients taking nintedanib ( n  = 107) or pirfenidone ( n  = 190), 211 (71.0%) had discontinued anti-fibrotic therapy ⩽ 5 medication half-lives before transplant. Anastomotic and sternal dehiscence occurred only in this group (anastomotic: 11 patients [5.2%], p  = 0.031 vs patients with longer time between discontinuation of anti-fibrotic medication and transplant; sternal: 12 patients [5.7%], p  = 0.024). No differences were observed in surgical wound dehiscence, length of hospital stay, or survival to discharge between groups with a shorter versus longer time between discontinuation of anti-fibrotic therapy and transplant. Conclusion: Anastomotic and sternal dehiscence only occurred in patients with idiopathic pulmonary fibrosis who discontinued anti-fibrotic therapy < 5 medication half-lives before transplant. The frequency of other intra-operative and post-transplant complications did not appear to differ depending on when anti-fibrotic therapy was discontinued. Registration: clinicaltrials.gov NCT04316780: https://clinicaltrials.gov/ct2/show/NCT04316780